Integrating the Impact of Digital Media and Social Networks on Human Communication and Behavior - Haoniyao Jehlani (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
The effects of social media and other forms of online communication on individual and group dynamics are investigated. Five hundred individuals were surveyed to gather data on the effects of social media on mental health, online activism, digital citizenship, and other pertinent issues. The aim of this article is to investigate the effects of social media and other forms of online communication on individual and group dynamics. The findings indicate that digital media can have both positive and negative effects on consumers and that the relationship between media and human interaction is complex. The majority of respondents identified online activism as a potent instrument for social change, and almost all agreed that digital citizenship is essential for the safe and ethical use of digital technologies. Numerous individuals reported negative outcomes as a result of excessive social media utilization, indicating the prevalence of social media addiction. Last but not least, the study found that social comparison is a significant factor in both social media addiction and adverse mental health effects. These findings highlight the importance of individuals acquiring digital literacy skills, monitoring their online behavior, and making an effort to utilize digital media in a positive manner. Understanding the effects of digital media on human communication and behavior is crucial for developing countermeasures.